Coexistence of Two blaNDM–5 Genes Carried on IncX3 and IncFII Plasmids in an Escherichia coli Isolate Revealed by Illumina and Nanopore Sequencing - Yang, Lang; Lin, Yanfeng; Lu, Lanfen; Xue, Mei; Ma, Hui; Guo, Xuguang; Wang, Kaiying; Li, Peihan; Du, Xinying; Qi, Kezong; Li, Peng; Song, Hongbin (Frontiers in Microbiology, 2020)
The emergence of carbapenem-resistant Enterobacteriaceae poses a significant threat to public health worldwide. Here, we reported a multidrug-resistant Escherichia coli strain with two different blaNDM–5-carrying plasmids from China. Illumina short-read and MinION long-read whole genome sequencing were performed. Genomic analysis found that one blaNDM–5 gene together with mphA was located on a 55-kb IncX3 plasmid, while the other blaNDM–5 gene was on a novel 68-kb IncFII plasmid. Susceptibility testing and quantitative reverse transcription PCR results further indicated that the transconjugants with the IncX3 plasmid exhibited higher-level carbapenem resistance and expression of blaNDM–5 than those with both plasmids or the IncFII plasmid. Two other β-lactamase genes (blaCTX–M–15 and blaOXA–1) were also detected on another 160-kb IncF plasmid. This is the first report of coexistence of two blaNDM–5-carrying plasmids in a single bacterial isolate, highlighting the genetic complexity of NDM-5 carbapenemase circulation, and the urgent need for continued active surveillance.